Effect of solvent state and isothermal conditions on gelation of methylcellulose hydrogels - Joshi, Sunil Chandrakant (2015)
In this study, thermal behavior of aqueous solutions of methyl cellulose (MC) at a constant temperature of 50°C was analyzed. Various samples were studied for two consecutive heating–cooling cycles. The experiments with the solutions prepared using cold de-ionized (DI) water showed that the rate of gelation was higher for higher MC concentrations. However, the rate was slower during the first heating–cooling cycle than during the second cycle. The possible reasons behind such observations are discussed. Various MC solutions prepared using hot DI water were studied for understanding the role of the solvent state in the isothermal gelation process. The gelation of these MC solutions started at a lower MC concentration and resulted in a higher gelation rate. The gelation mechanism responsible for such effects is explored and presented. Finally, a gel-indexing method is proposed to provide a quantitative measure of the gelation state of all the MC gels.